Targeting the epidermal growth factor receptor using IgM antibodies: toward next generation cancer immunotherapy - Somboon, Kamolrat; Bond, Peter J.; Samsudin, Firdaus (Frontiers in Immunology, 2026)
Immunoglobulin G (IgG) monoclonal antibodies dominate current cancer immunotherapy but face challenges including resistance development, limited tumor penetration, and suboptimal avidity. In contrast, the pentameric or hexameric architecture of immunoglobulin M (IgM) offers up to twelve antigen-binding sites and potent complement activation, positioning IgM as a promising next-generation therapeutic scaffold. Here, we present integrative structural modeling and multiscale molecular dynamics simulations of IgM versions of Cetuximab and Matuzumab targeting the epidermal growth factor receptor (EGFR), a clinically validated oncogenic driver. Our analyses reveal that IgM antibodies maintain a rigid, glycan-stabilized Fc core while their Fab domains exhibit high mobility, enabling multivalent EGFR binding. Compared with IgG, IgM antibodies demonstrated enhanced binding avidity, prolonged receptor engagement, and slower dissociation kinetics. These properties suggest superior therapeutic durability and potential to overcome current limitations of IgG-based therapies. By providing mechanistic insight into how IgM isotypes can improve therapeutic engagement with tumor-associated antigens, our study supports the development of IgM antibodies as a new class of cancer immunotherapies.